Recording orchestra and other classical music ensembles - King, Richard (Richard Lemprière) (Routledge, 2017)
Recording Orchestra and Other Classical Music Ensembles explores techniques and methodologies specific to recording classical music. Whether a newcomer or a seasoned engineer looking to refine their skills, this book speaks to all levels of expertise and covers every aspect of recording symphonic and concerto repertoire, opera, chamber music, and solo piano. With a focus on the orchestra as an instrument and sound source, this book features sections on how to listen, understanding microphones, concert halls, orchestra seating arrangements, how to set up the monitoring environment, and how to approach recording each section of the orchestra. Recording Orchestra provides concise information on preparing for a recording session, the role of the producer, mixing techniques, and includes a "quick-start" reference guide with suggested setups aimed at helping introduce the reader to the recording process. A companion website, featuring audio examples of various techniques, reinforces concepts discussed throughout the book. The content of the book includes: Clear, practical advice in plain language from an expert in classical music recording, multiple Grammy award winning recording engineer, and university professor The "secret of recording": a collection of practical recording techniques that have been proven to be highly successful in the field, on many occasions Never before published information written by an industry veteran with over twenty five-years of experience in classical music recording Specific techniques and strategies for recording orchestra, opera, wind symphony, chorus, string quartet, and other common classical music ensembles